Pemenuhan Hak Pembebasan Bersyarat Narapidana Perempuan Dalam Perspektif Undang-Undang No. 22 Tahun 2022 Tentang Pemasyarakatan - Marisa Jemmy; Gessia Ferandha (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
The correctional system in Indonesia is a subsystem of the criminal justice system that serves to rehabilitate, protect, and facilitate the reintegration of prisoners so that they can return to society as responsible citizens. One of the rights stipulated in Law Number 22 of 2022 on Corrections is conditional release, which allows inmates to serve the remainder of their sentence outside correctional facilities under the supervision of correctional authorities. The research questions in this study are: First, how is the fulfillment of the right to conditional release for female inmates addressed under Law No. 22 of 2022 on Corrections? Second, what are the challenges in fulfilling the right to conditional release for female inmates under Law No. 22 of 2022 on Corrections? Third, what efforts can be made to overcome the challenges in fulfilling the conditional release rights of female prisoners from the perspective of Law Number 22 of 2022 on Corrections? The method used in this study is a normative legal approach with a regulatory and conceptual approach, using secondary data obtained through document analysis conducted qualitatively. The results of this study indicate that the fulfillment of conditional release rights is in accordance with the provisions of Law Number 22 of 2022, but in practice, it still faces several obstacles such as administrative delays, lack of guarantors, incomplete court documents, and overcrowding in correctional institutions. Efforts to address these challenges include strengthening coordination between correctional institutions, optimizing administrative services, disseminating regulations to inmates and their families, and enhancing the role of the community in accepting the reintegration of inmates. Thus, conditional release is not only a legal right but also a tool for social rehabilitation in line with the objectives of the Correctional System.